2010
DOI: 10.1371/journal.pone.0014384
|View full text |Cite
|
Sign up to set email alerts
|

High Accuracy Decoding of Movement Target Direction in Non-Human Primates Based on Common Spatial Patterns of Local Field Potentials

Abstract: BackgroundThe current development of brain-machine interface technology is limited, among other factors, by concerns about the long-term stability of single- and multi-unit neural signals. In addition, the understanding of the relation between potentially more stable neural signals, such as local field potentials, and motor behavior is still in its early stages.Methodology/Principal FindingsWe tested the hypothesis that spatial correlation patterns of neural data can be used to decode movement target direction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 43 publications
(57 reference statements)
5
43
0
Order By: Relevance
“…The fact that critical information for decoding lower limb kinematics is contained in the smoothed AM in the lower half of the so-called delta band (i.e., 0.1-4 Hz) is consistent with recent EEG, electrocorticographic (ECoG), and local field potential (LFP) upper limb movement decoding studies that use the fluctuations in the amplitude of highly smoothed signals for decoding (Acharya et al 2010;Ball et al 2009;Ince et al 2010;Lv et al 2010;Waldert et al 2008;Zhuang et al 2010). It is also consistent with observations by Gwin et al (2010), who showed that meaningful changes during walking or running occur at low frequencies (Ͻ10 Hz) in high-density EEG.…”
Section: Discussionsupporting
confidence: 71%
“…The fact that critical information for decoding lower limb kinematics is contained in the smoothed AM in the lower half of the so-called delta band (i.e., 0.1-4 Hz) is consistent with recent EEG, electrocorticographic (ECoG), and local field potential (LFP) upper limb movement decoding studies that use the fluctuations in the amplitude of highly smoothed signals for decoding (Acharya et al 2010;Ball et al 2009;Ince et al 2010;Lv et al 2010;Waldert et al 2008;Zhuang et al 2010). It is also consistent with observations by Gwin et al (2010), who showed that meaningful changes during walking or running occur at low frequencies (Ͻ10 Hz) in high-density EEG.…”
Section: Discussionsupporting
confidence: 71%
“…For example, O'Leary and Hatsopoulos have shown very large interanimal differences in LFP-␤ measured in PMd (O'Leary and Hatsopoulos 2006). Second, LFP-␤ has often been found to be not as reliable as the low frequency bands for decoding performance during reach-andgrasp tasks (Bansal et al 2011;Ince et al 2010) because of its instability. Third, sometimes the LFP-␤ in premotor cortex might be completely absent, unlike in M1 (Spinks et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A number of recent studies have proposed the use of non-invasive methods, in particular the electroencephalography (EEG) signal, for decoding reaching directions (Mehring et al, 2003; Waldert et al, 2008; Ince et al, 2010) and continuous trajectories (Wolpaw and McFarland, 2004; Bradberry et al, 2010). Nevertheless most of these studies, in particular those focused on decoding movement direction (Connolly et al, 2003; Mehring et al, 2003; Musallam et al, 2004; Rickert et al, 2005; Rizzuto et al, 2005; Hammon et al, 2008; Waldert et al, 2008; Robinson et al, 2013), rely on cue-based protocols (i.e., where a “go” cue is used to instruct the subject to perform the movement at a fixed time).…”
Section: Introductionmentioning
confidence: 99%